1991
DOI: 10.1093/ije/20.2.416
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Grain Farming and Smoking on Lung Function and the Prevalence of Chronic Bronchitis

Abstract: The combined effect of grain farming and smoking on lung function and the prevalence of chronic bronchitis was examined in 1633 residents 20 to 65 years of age from the town of Humboldt, Saskatchewan. Multiple multivariate analysis indicated that in women grain farming and smoking had a significant synergistic effect on the values of forced expired volume in one second/forced vital capacity (FEV1/FVC), mid-expiratory flow rate (MMFR), flow rate at 50% and 25% of total volume (Vmax50 and Vmax25) after adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
3
19
1
1
Order By: Relevance
“…Daily cigarette consumption was highest among patients with CB. Neither occupation nor the place of living had detectable effects on the rate of CB, despite studies that have shown that some occupations increase the prevalence of CB [24][25][26][27][28][29][30][31], and other studies that have demonstrated differences in CB prevalence among geographical areas [32,33]. The present survey found differences only in CC and CE among people living either in the east of France or in Ile-de France.…”
Section: Discussioncontrasting
confidence: 80%
“…Daily cigarette consumption was highest among patients with CB. Neither occupation nor the place of living had detectable effects on the rate of CB, despite studies that have shown that some occupations increase the prevalence of CB [24][25][26][27][28][29][30][31], and other studies that have demonstrated differences in CB prevalence among geographical areas [32,33]. The present survey found differences only in CC and CE among people living either in the east of France or in Ile-de France.…”
Section: Discussioncontrasting
confidence: 80%
“…Chronic exposure to grain dust and cigarette smoking are both associated with chronic airways disease. CHEN et al [28] reported an interactive effect between grain farming exposure and smoking on lung function and chronic bronchitis in females but not males. Heavy cigarette smokers have been reported to have a higher rate of emergency department visits for respiratory disease following days of high ozone levels compared with nonsmokers [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that farmers growing different types of grain and soybeans (1,2) and farmers raising livestock (3) have respiratory symptoms and diseases. This may have considerable impact worldwide considering there are approximately 3 million farm workers in the United States alone.…”
Section: Introductionmentioning
confidence: 99%